The summer wind - Monroe, Mary Alice (New York : Gallery Books, 2014)
Marietta Colson Muir, a dowager of Charleston society has retired to her historic summer home on Sullivan's Island called Conquest. Her three granddaughters Carson, Eudora, and Harper are there when Sullivan's is hit with a tropical storm.
Includes readers group guide.
"The lowcountry summer trilogy"--cover.
Keywords: Grandmothers -- Fiction; Granddaughters -- Fiction; Sisters -- Fiction; Self-realization in women -- Fiction; Sullivan's Island (S.C. : Island) -- Fiction; Domestic fiction; Psychological fiction